Taxpayer Experience as a Mediator Between Its Antecedents and Taxpayer Satisfaction - Sari, Yohana; Rachman, M Yudy (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This study aims to determine the direct influence of servicescape and service quality on taxpayer experience. It also seeks to ascertain the direct impact of servicescape and service quality on taxpayer satisfaction. Additionally, the study aims to explore the indirect effect of taxpayer experience as a mediator in the relationship between servicescape and service quality on taxpayer satisfaction. The study sample consisted of 100 respondents of local taxpayers in Banjarmasin City. Path analysis was chosen as the method to assist in analyzing the data. The results of the study successfully demonstrated that servicescape and service quality have a direct influence on the taxpayer experience. From the perspective of taxpayer satisfaction, the research also confirmed the direct effect of servicescape and service quality on taxpayer satisfaction. Apart from direct effects, the study examined the indirect effects of servicescape and service quality on taxpayer satisfaction, with taxpayer experience acting as a mediating variable. The study was able to prove that servicescape indirectly affects taxpayer satisfaction through taxpayer experience as a mediator. Lastly, it also established that service quality has an indirect influence on taxpayer satisfaction through taxpayer experience. Keywords: Servicescape; Service Quality; Taxpayer Experience; Taxpayer Satisfaction; Local Taxes